A Drug Repositioning Approach Identifies a Combination of Compounds as a Potential Regimen for Chronic Lymphocytic Leukemia Treatment - Nehdi, Atef; Samman, Nosaibah; Mashhour, Abdullah; Alhallaj, Alshaimaa; Trivilegio, Thadeo; Gul, Sheraz; Reinshagen, Jeanette; Alaskar, Ahmed; Gmati, Gamal; Abuelgasim, Khadega A.; Mansour, Fatmah; Boudjelal, Mohamed (Frontiers in Oncology, 2021)
Drug repositioning is a promising and powerful innovative strategy in the field of drug discovery. In this study, we screened a compound-library containing 800 Food and Drug Administration approved drugs for their anti-leukemic effect. All screening activities made use of human peripheral blood mononuclear cells (PBMCs), isolated from healthy or leukemic donors. Compounds with confirmed cytotoxicity were selected and classified in three groups: i) anti-neoplastic compounds which are drugs used in leukemia treatment, ii) compounds known to have an anti-cancer effect and iii) compounds demonstrating an anti-leukemic potential for the first time. The latter group was the most interesting from a drug repositioning perspective and yielded a single compound, namely Isoprenaline which is a non-selective β-adrenergic agonist. Analysis of the cytotoxic effect of this drug indicated that it induces sustainable intracellular ATP depletion leading, over time, to necrotic cell death. We exploited the Isoprenaline-induced intracellular ATP depletion to sensitize primary leukemic cells to fludarabine (purine analogue) and Ibrutinib (Bruton's tyrosine kinase inhibitor) treatment. In-vitro treatment of primary leukemic cells with a combination of Isoprenaline/fludarabine or Isoprenaline/Ibrutinib showed a very high synergistic effect. These combinations could constitute a new efficient regimen for CLL treatment following successful evaluation in animal models and clinical trials.